Fragment Intrinsic Spins and Fragments’ Relative Orbital Angular Momentum in Nuclear Fission - Bulgac, Aurel; Abdurrahman, Ibrahim; Godbey, Kyle; Stetcu, Ionel (Physical review letters, 2022)
We present the first fully unrestricted microscopic calculations of the primary fission fragment intrinsic spins and of the fission fragments' relative orbital angular momentum for ^{236}U^{*}, ^{240}Pu^{*}, and ^{252}Cf using the time-dependent density functional theory framework. Within this microscopic approach, free of restrictions and unchecked assumptions and which incorporates the relevant physical observables for describing fission, we evaluate the triple distribution of the fission fragment intrinsic spins and of their fission fragments' relative orbital angular momentum and show that their dynamics is dominated by their bending collective modes in contradistinction to the predictions of the existing phenomenological models and some interpretations of experimental data.